Online Marketing Readiness of MSMEs in Indonesia: A Perspective of Technology Organizational Environmental Framework - Asmawati Asmawati; Imam Ahmad; Emi Suwarni; Debby Alita; Cut Delsi Hasrina (Journal of Economics, Business, and Accountancy Ventura, 2024)
Micro, Small, and Medium-sized Enterprises (MSMEs) play a crucial role in the economic landscape of tourism areas, offering collective services that enhance tourist experiences and convenience at destinations. One key effort to promote tourism is enhancing the technological readiness of MSMEs. This study aims to evaluate the preparedness of MSMEs to adopt e-commerce technology. Data was gathered through interviews and questionnaires distributed randomly to 184 business operators. The research utilized the Technology Organizational Environmental (TOE) framework, encompassing ten indicators identified from various sources. Data analysis was conducted using Structural Equation Modeling (SEM) with four hypotheses. The findings reveal that both organizational readiness and external environmental support have a positive impact on technology adoption readiness. Furthermore, organizational readiness significantly mediates the relationship between environmental support and technological readiness. Therefore, it is essential to develop the organizational readiness of MSMEs to facilitate the adoption of e-commerce technology.